Polyphenol and polysaccharide copolymerization method based on plasma induction
Through the plasma-induced polyphenol polysaccharide copolymerization method, the problem that polyphenol and polysaccharide copolymer preparation methods in the prior art is difficult to take into account both green and efficient, and the efficient and non-toxic polyphenol-polysaccharide copolymer preparation is achieved, which improves the Bioactivity and solubility.
Patent Information
- Application Number
- CN202411464542.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing preparation methods for polyphenol and polysaccharide copolymers have problems that are difficult to take into account both green and efficient, such as the risk of exposure of chemical reagent-induced coupling, low enzyme catalytic efficiency, and long radical induction reaction time.
Using the plasma-induced polyphenol polysaccharide copolymerization method, the high-energy active substances such as hydroxyl radicals, reactive nitrogen, and reactive oxygen generated by plasma are used to activate polysaccharides and polyphenols in the presence of high-energy active substances, and can be simply stirred. Prepare polyphenol-polysaccharide copolymers with short reaction time, high efficiency and no toxic and harmful reagents are required.
The green and efficient preparation of polyphenol-polysaccharide copolymers is achieved, and the grafting efficiency is even greater than that of the free radical induction method. The reaction time is shorter, the efficiency is higher, and the need for toxic and harmful reagents is not required, which significantly improves biological activity and solubility.
Smart Images

Figure CN119306856A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyphenol and polysaccharide composites, and in particular to a polyphenol and polysaccharide copolymerization method based on plasma induction. Background Art
[0002] Monosaccharides can be defined as polyhydroxy aldehydes or polyhydroxy ketones, while polysaccharides are natural biomacromolecules formed by the polymerization of monosaccharides through various glycosidic bonds. Due to the presence of multiple hydroxyl groups and multiple conformations, polysaccharides have a range of functional properties, including emulsification, gelation, and anticancer activity. Due to their high degree of polymerization and large molecular weight, polysaccharides are poorly soluble in water and difficult to absorb in the intestine, which severely limits their biologically active applications. In addition, the antioxidant properties of polysaccharides are generally not very obvious. Due to these limitations, it is particularly important to modify polysaccharides in some way to improve their applications. For example, chitosan is a natural cationic polysaccharide with very excellent antibacterial properties and the ability to promote wound healing, but the naturally occurring side chain structure of chitosan and its strong hydrogen bonds make chitosan less soluble under neutral and alkaline conditions and have low bioavailability.
[0003] Polyphenols are key secondary metabolites found primarily in the leaves and fruits of higher plants. They typically contain at least two phenolic hydroxyl groups, and the p-π conjugated structure of these groups makes polyphenols highly electron-loaded. This property endows polyphenols with significant anti-inflammatory and anti-cancer effects. In addition, polyphenols can alleviate chronic diseases such as diabetes and cardiovascular disease by neutralizing free radicals and combating oxidative stress. Although polyphenols have potent biological activities, several major drawbacks hinder their widespread application. Notably, polyphenols have low solubility at standard pH, are sensitive to light and heat, and have limited bioavailability in vivo.
[0004] Polyphenols and polysaccharides have a variety of multifunctional activities, some of which have a common mechanism of action, and their combination has the potential to produce stronger biological activities. Some of the disadvantages of polyphenols and polysaccharides can also be avoided in the form of copolymers. In fact, there are a large number of natural polyphenol-polysaccharide copolymers in plants, which are linked together by covalent or non-covalent interactions and exhibit a variety of biological activities. However, due to the complex structure of natural copolymers, it is difficult to develop and study them. People are increasingly interested in synthesizing polyphenol-polysaccharide copolymers with known structures and applying them.
[0005] At present, there are four main methods for preparing polyphenol-polysaccharide copolymers, namely chemical reagent induced coupling, enzyme catalyzed coupling, free radical induced crosslinking, and electrochemical guided crosslinking. And there are still some problems with the preparation methods of these copolymers. For example, the chemical reagent method has a certain exposure risk, the enzyme method has a low efficiency, and the free radical method has a long reaction time. Summary of the invention
[0006] In order to solve the green and high efficiency problems that cannot be taken into account in the existing polyphenol and polysaccharide composite technology, and to realize the preparation of polyphenol-polysaccharide copolymers in a green and efficient method, the present invention provides a polyphenol-polysaccharide copolymerization method based on plasma induction. The present invention utilizes plasma that can produce a large number of high-energy active substances such as hydroxyl radicals, active nitrogen, and active oxygen, so that polysaccharides and polyphenols are activated under the condition of the presence of high-energy active substances, induce the formation of polysaccharide-polyphenol complexes, and prepare polyphenol-polysaccharide copolymers by simple stirring of polysaccharides and polyphenols. The copolymer prepared by the method provided by the present invention has a high grafting efficiency, which can reach or even exceed the grafting efficiency of the free radical induction method. In addition, the method of the present invention not only has a shorter reaction time and a higher reaction efficiency, but also does not require any toxic and harmful reagents, thereby realizing the green and efficient preparation of polyphenol-polysaccharide copolymers.
[0007] The specific technical scheme of the present invention is: In one aspect, the present invention provides a method for copolymerizing polyphenols and polysaccharides based on plasma induction, comprising the following steps: Step S1: dissolving polysaccharides and polyphenols in a solvent, and mixing them to obtain a mixed solution; Step S2: Plasma treatment is introduced into the mixed solution for a period of time; Step S3: taking the mixed liquid after the plasma treatment and stirring it; Step S4: Dialysis and freeze-drying to obtain a polyphenol-polysaccharide copolymer.
[0008] The present invention utilizes plasma that can generate a large amount of high-energy active substances such as hydroxyl free radicals, active nitrogen, and active oxygen to activate polysaccharides and polyphenols under the condition of the presence of high-energy active substances, induce the formation of polysaccharide-polyphenol complexes, and prepare polyphenol-polysaccharide copolymers by simply stirring polysaccharides and polyphenols. The copolymer prepared by the method provided by the present invention has a high grafting efficiency, which can reach or even exceed the grafting efficiency of the free radical induction method. In addition, the method of the present invention not only has a shorter reaction time and a higher reaction efficiency, but also does not require any toxic and harmful reagents, thereby realizing the green and efficient preparation of polyphenol-polysaccharide copolymers.
[0009] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, in step S2, the treatment is carried out by nitrogen plasma.
[0010] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, in step S2, plasma treatment is performed by a jet plasma spray gun, specifically, the exhaust port of the jet plasma spray gun is placed below the liquid surface of the mixed liquid to perform plasma discharge.
[0011] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, the plasma treatment time is 5 to 30 min.
[0012] On the other hand, specifically, the present invention takes the copolymerization reaction of gallic acid and chitosan as an example, and provides a method for preparing gallic acid-chitosan copolymer based on plasma induction, comprising the following steps: (1) dissolving chitosan and gallic acid in a solvent and mixing them to obtain a mixed solution; (2) placing the exhaust port of the jet plasma spray gun below the liquid surface of the mixed solution and turning on the spray gun to perform plasma discharge; wherein nitrogen gas is introduced into the jet plasma spray gun; (3) quickly placing the mixed solution after plasma treatment in a high-temperature water bath for stirring and reaction; (4) Dialysis and freeze-drying to obtain gallic acid-chitosan copolymer.
[0013] As a preferred embodiment of the above preparation method, in step (1), the solvent is an acetic acid solution, and the mass percentage of the acetic acid solution is 0.5-2%.
[0014] As a preferred embodiment of the above preparation method, in step (2), the exhaust port of the jet plasma spray gun is placed 1 to 4 cm below the liquid surface of the mixed solution.
[0015] As a preferred embodiment of the above preparation method, in step (2), the nitrogen gas is introduced at a flow rate of 2 to 8 L / min.
[0016] As a preferred embodiment of the above preparation method, in step (2), the discharge power of the jet plasma spray gun is 100-130 W, and the discharge time is 5-30 min.
[0017] As a preferred embodiment of the above preparation method, in step (3), the temperature of the high temperature water bath is 60-90° C., and the stirring time is 1-4 h.
[0018] As a preferred embodiment of the above preparation method, in step (4), dialysis uses a dialysis bag with a specification of 3500 Da~140 KDa; the dialysis time is 24~96 h, preferably 48~72 h.
[0019] Compared with the prior art, the present invention has the following technical effects: (1) The present invention utilizes plasma that can generate a large amount of high-energy active substances such as hydroxyl free radicals, active nitrogen, and active oxygen to activate polysaccharides and polyphenols in the presence of high-energy active substances, thereby inducing the formation of polysaccharide-polyphenol complexes, so that polysaccharides and polyphenols can be prepared into polyphenol-polysaccharide copolymers by simple stirring. The copolymer prepared by the method provided by the present invention has a high grafting efficiency, which can reach or even exceed the grafting efficiency of the free radical induction method. In addition, the method of the present invention not only has a shorter reaction time and a higher reaction efficiency, but also does not require any toxic or harmful reagents, thereby realizing the green and efficient preparation of polyphenol-polysaccharide copolymers.
[0020] (2) The present invention also clarifies the process conditions for plasma-induced copolymerization of polysaccharides and polyphenols by taking the preparation of a copolymer of gallic acid and chitosan as an example. In the preparation method of gallic acid-chitosan copolymer, when nitrogen plasma is used to induce copolymerization and the nitrogen inlet flow rate is 2-8 L / min, the grafting rate is relatively high, and 4-5 L / min is further preferred; the temperature of the high-temperature water bath is preferably 60-90°C, and the water bath reaction time is preferably 1-4h, and the grafting rate is relatively high. The present invention induces the copolymerization of gallic acid and chitosan by plasma, so that gallic acid can be covalently grafted onto the primary amine of chitosan in the form of an amide bond to obtain a gallic acid-chitosan copolymer with a higher hydroxyl radical scavenging rate, that is, it has a better hydroxyl radical scavenging ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a process flow chart for preparing gallic acid-chitosan copolymer; Figure 2 is the UV-visible spectrum of gallic acid-chitosan copolymer; Figure 3 is the Fourier transform infrared spectrum of gallic acid-chitosan copolymer; Figure 4 This is a comparison chart of DPPH free radical scavenging rate of gallic acid-chitosan copolymer; Figure 5 This is a comparison chart of the ABTS free radical scavenging rate of gallic acid-chitosan copolymer; Figure 6 This is a comparison chart of the hydroxyl radical scavenging rate of gallic acid-chitosan copolymer; Figure 7 This is the solubility change diagram of gallic acid-chitosan copolymer. DETAILED DESCRIPTION
[0022] The present invention provides a plasma-induced polyphenol-polysaccharide copolymerization method, comprising the following steps: Step S1: dissolving polysaccharides and polyphenols in a solvent, and mixing them to obtain a mixed solution; Step S2: Plasma treatment is introduced into the mixed solution for a period of time; Step S3: taking the mixed liquid after the plasma treatment and stirring it; Step S4: Dialysis and freeze-drying to obtain a polyphenol-polysaccharide copolymer.
[0023] The present invention utilizes plasma that can generate a large amount of high-energy active substances such as hydroxyl free radicals, active nitrogen, and active oxygen to activate polysaccharides and polyphenols under the condition of the presence of high-energy active substances, induce the formation of polysaccharide-polyphenol complexes, and prepare polyphenol-polysaccharide copolymers by simply stirring polysaccharides and polyphenols. The copolymer prepared by the method provided by the present invention has a high grafting efficiency, which can reach or even exceed the grafting efficiency of the free radical induction method. In addition, the method of the present invention not only has a shorter reaction time and a higher reaction efficiency, but also does not require any toxic and harmful reagents, thereby realizing the green and efficient preparation of polyphenol-polysaccharide copolymers.
[0024] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, in step S2, the treatment is carried out by nitrogen plasma.
[0025] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, in step S2, plasma treatment is performed by a jet plasma spray gun, specifically, the exhaust port of the jet plasma spray gun is placed below the liquid surface of the mixed liquid to perform plasma discharge.
[0026] As a preferred embodiment of the polyphenol-polysaccharide copolymerization method, the plasma treatment time is 5 to 30 min.
[0027] Specifically, the present invention takes the copolymerization reaction of gallic acid and chitosan as an example, and provides a method for preparing gallic acid-chitosan copolymer based on plasma induction. The preparation process is as follows: Figure 1 As shown, the following steps are included: (1) dissolving chitosan and gallic acid in a solvent and mixing them to obtain a mixed solution; (2) placing the exhaust port of the jet plasma spray gun below the liquid surface of the mixed solution and turning on the spray gun to perform plasma discharge; wherein nitrogen gas is introduced into the jet plasma spray gun; (3) quickly placing the mixed solution after plasma treatment in a high-temperature water bath for stirring and reaction; (4) Dialysis and freeze-drying to obtain gallic acid-chitosan copolymer.
[0028] As a preferred method for preparing gallic acid-chitosan copolymer, in step (1), the solvent is an acetic acid solution, and the mass percentage of the acetic acid solution is 0.5-2%.
[0029] As a preferred method for preparing gallic acid-chitosan copolymer, in step (1), the molar ratio of chitosan to gallic acid is 1:(1-6), more preferably 1:(3-4).
[0030] As a preferred method for preparing gallic acid-chitosan copolymer, in step (2), the exhaust port of the jet plasma spray gun is placed 1 to 4 cm below the liquid surface of the mixed solution.
[0031] As a preferred method for preparing gallic acid-chitosan copolymer, in step (2), the nitrogen gas is introduced at a flow rate of 2-8 L / min.
[0032] As a preferred method for preparing gallic acid-chitosan copolymer, in step (2), the discharge power of the jet plasma spray gun is 100-130 W, and the discharge time is 5-30 min.
[0033] As a preferred method for preparing gallic acid-chitosan copolymer, in step (3), the temperature of the high-temperature water bath is 60-90° C., and the stirring time is 1-4 h.
[0034] As a preferred method for preparing gallic acid-chitosan copolymer, in step (4), dialysis uses a dialysis bag with a specification of 3500 Da~140 KDa; the dialysis time is 24~96 h, preferably 48~72 h.
[0035] The present invention takes the preparation of the copolymer of gallic acid and chitosan as an example, and clarifies the process conditions for plasma-induced copolymerization of polysaccharides and polyphenols. In the preparation method of gallic acid-chitosan copolymer, when nitrogen plasma is used to induce copolymerization and the nitrogen flow rate is 2-8 L / min, the grafting rate is relatively high, and 4-5 L / min is further preferred; the temperature of the high-temperature water bath is preferably 60-90°C, and the water bath reaction time is preferably 1-4h, and the grafting rate is relatively high. The present invention induces the copolymerization of gallic acid and chitosan by plasma, so that gallic acid can be covalently grafted on the primary amine of chitosan in the form of an amide bond, and a gallic acid-chitosan copolymer is obtained, which has a higher hydroxyl radical scavenging rate, that is, has a better hydroxyl radical scavenging ability.
[0036] The present invention characterizes and identifies the structure of the purified polyphenol-polysaccharide copolymer by ultraviolet-visible spectroscopy and Fourier transform infrared spectroscopy. Polyphenol has a structure of a benzene ring and a phenolic hydroxyl group, wherein there are π-π and p-π conjugated electron systems. After absorbing the energy of ultraviolet light, these two electron systems undergo electron transitions in the range of 200-600 nm, thereby generating absorption peaks. However, normal polysaccharides do not have particularly obvious performance within this range. The copolymer after the polysaccharide is covalently grafted with the polyphenol also has the structure of the polyphenol benzene ring and even the phenolic hydroxyl group. The polyphenol-polysaccharide copolymer has a new covalent bond after covalent connection, and some changes occur in the functional groups. Therefore, the structure of the copolymer can be effectively verified by using ultraviolet-visible spectroscopy and Fourier transform infrared spectroscopy.
[0037] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.
[0038] In the following examples, the determination of the grafting rate involved is carried out according to the following method: the freeze-dried copolymer is prepared into a sample solution with a concentration of 1.0 mg / mL, 1.0 mL of the sample solution is taken in a graduated test tube, 6.0 mL of deionized water and 1 mL of Folin phenol reagent are added in sequence, shaken and allowed to stand for 6 min. Then 4.0 mL of 10.6% Na2CO3 solution is added, shaken and stored in the dark for 60 min. After the color development is completed, it is diluted to 25 mL with deionized water, and its absorbance A is measured at a wavelength of 760 nm. The grafting rate is calculated according to the following formula: Grafting rate (%) = Wherein, a is the content of gallic acid per gram of sample calculated based on the absorbance of the samples of the corresponding group and the standard curve, in mg / g; m1 is the mass of the freeze-dried copolymer in each group, in g; and m0 is the mass of gallic acid added to each group, in g.
[0039] Example 1 This embodiment provides a gallic acid-chitosan copolymer, which is prepared according to the following steps: (1) Weigh 200 mg chitosan powder and gallic acid powder in a molar ratio of 1:3 to an accuracy of 0.001 g, and dissolve the chitosan powder and gallic acid powder in 1% (mass ratio) acetic acid solution; (2) Magnetic stirring was performed at 240 rpm for 22 h to obtain a uniform mixed solution of gallic acid and chitosan; (3) The exhaust port of the jet plasma spray gun was placed 2.5 cm below the liquid surface of the mixed solution, and nitrogen was introduced so that the nitrogen flow rate was maintained at 5 L / min. The plasma discharge power was controlled at 110 W and the plasma discharge time was controlled at 20 min. (4) The plasma-treated mixture was quickly placed in an 80°C water bath and stirred for 2 h at a rate of 300 rpm. (5) The copolymer obtained after the water bath reaction was dialyzed in a 3500 Da dialysis bag for 72 h and then freeze-dried to obtain a purified gallic acid-chitosan copolymer.
[0040] It was determined that the grafting rate of this embodiment was 27.83%.
[0041] Example 2 This embodiment provides a gallic acid-chitosan copolymer, and its preparation is different from that of Example 1 in that: The molar ratio of chitosan to gallic acid is 1: 1. Other conditions are the same as in Example 1.
[0042] It was determined that the grafting rate of this embodiment was 12.77%.
[0043] Example 3 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of embodiment 1 except that the molar ratio of chitosan to gallic acid is 1:6. Other conditions are the same as those of embodiment 1.
[0044] It was determined that the grafting rate of this embodiment was 13.13%.
[0045] Example 4 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of embodiment 1 except that the molar ratio of chitosan to gallic acid is 1:4. Other conditions are the same as those of embodiment 1.
[0046] It was determined that the grafting rate of this embodiment was 21.30%.
[0047] Combining the analysis of Examples 1 to 4, it can be seen that as a preferred method for preparing the gallic acid-chitosan copolymer, the molar ratio of chitosan to gallic acid is 1:(1-6), and more preferably 1:(3-4).
[0048] Example 5 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of the embodiment 1 except that the plasma discharge time is 30 minutes. Other conditions are the same as those of the embodiment 1.
[0049] It was determined that the grafting rate of this embodiment was 21.54%.
[0050] Example 6 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of the embodiment 1 except that the plasma discharge time is 15 minutes. Other conditions are the same as those of the embodiment 1.
[0051] It was determined that the grafting rate of this embodiment was 16.21%.
[0052] Example 7 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of the embodiment 1 except that the plasma discharge time is 8 minutes. Other conditions are the same as those of the embodiment 1.
[0053] It was determined that the grafting rate of this embodiment was 11.86%.
[0054] Example 8 This embodiment provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of embodiment 1 except that the molar ratio of chitosan to gallic acid is 1:6, and the plasma discharge time is 8 minutes. Other conditions are the same as those of embodiment 1.
[0055] It was determined that the grafting rate of this embodiment was 10.25%.
[0056] Combined with the analysis of Example 1, Example 3, and Example 6-7, it can be seen that when the molar ratio of chitosan and gallic acid and the plasma discharge time are controlled under the optimal conditions, the grafting rate can reach the optimal (Example 1); when the molar ratio of chitosan and gallic acid and the plasma discharge time are controlled under the optimal conditions, the grafting rate will be greatly reduced (Example 7).
[0057] Example 9 This example provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of Example 1 except that the water bath temperature is 70° C., and the water bath stirring reaction time is 3 h. Other conditions are the same as those of Example 1.
[0058] It was determined that the grafting rate of this embodiment was 17.76%.
[0059] Example 10 This example provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of Example 1 except that the nitrogen flow rate is 4 L / min. Other conditions are the same as those of Example 1.
[0060] It was determined that the grafting rate of this embodiment was 21.67%.
[0061] Embodiment 11 This example provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of Example 1 except that the nitrogen flow rate is 2 L / min. Other conditions are the same as those of Example 1.
[0062] It was determined that the grafting rate of this embodiment was 13.86%.
[0063] Example 12 This example provides a gallic acid-chitosan copolymer, and the preparation thereof is different from that of Example 1 except that the nitrogen flow rate is 8 L / min. Other conditions are the same as those of Example 1.
[0064] It was determined that the grafting rate of this embodiment was 10.02%.
[0065] Combining the analysis of Example 1 and Examples 10 to 12, it can be seen that when the nitrogen flow rate is preferably 2 to 8 L / min, the flow rate is set to 4 to 5 L / min, which can further improve the grafting rate.
[0066] Comparative Example 1 This comparative example provides a gallic acid-chitosan copolymer, the preparation of which is different from that of Example 1 except that the jet plasma treatment in step (3) is not performed. Other conditions are the same as those of Example 1.
[0067] It was determined that the grafting rate of this comparative example was 2.36%.
[0068] Comparative Example 2 This comparative example provides a gallic acid-chitosan copolymer, the preparation of which is different from that of Example 1 except that the water bath reaction in step (4) is not performed. Other conditions are the same as those of Example 1.
[0069] It was determined that the grafting rate of this comparative example was 2.11%.
[0070] Comparative Example 3 This comparative example provides a gallic acid-chitosan copolymer, the preparation of which is different from that of Example 1, except that the jet plasma treatment time of step (3) is increased by 2 h (i.e., the jet plasma treatment time is 20 min + 2 h), and the water bath stirring operation of step (4) is not performed. Other conditions are the same as those of Example 1.
[0071] It was determined that the grafting rate of this comparative example was 3.14%.
[0072] Combined with the analysis of Example 1 and Comparative Examples 1 to 3, it can be seen that the jet plasma treatment can induce the formation of gallic acid-chitosan copolymer, so that gallic acid and chitosan can be prepared by simple stirring to obtain gallic acid-chitosan copolymer. The role of jet plasma treatment is to induce and activate gallic acid and chitosan. Gallic acid-chitosan copolymer still requires certain reaction conditions, that is, reacting in a high temperature water bath for a period of time.
[0073] Effect verification 1. Grafting verification of gallic acid-chitosan copolymer In this example, the structure of the purified copolymer was characterized and identified by UV-visible spectroscopy and Fourier transform infrared spectroscopy. The results showed that Examples 1 to 12 all successfully prepared gallic acid-chitosan copolymers.
[0074] (1) Ultraviolet spectrum characteristics Gallic acid-chitosan copolymer, gallic acid, and chitosan were respectively prepared into solutions with a concentration of 1.0 mg / mL with deionized water, and the UV spectrum of each group of samples was measured in the wavelength range of 200-600 nm at 25°C using a UV-visible spectrophotometer (GENESYS 150, Thermo Fisher Scientific, America). The results showed that gallic acid-chitosan copolymers were successfully prepared in Examples 1 to 9.
[0075] Figure 2 The UV spectra of gallic acid-chitosan copolymer (Example 11), gallic acid, and chitosan are shown in FIG. Figure 2 As shown in the figure, the full-band UV scan shows that chitosan has no obvious absorption peak in the wavelength range of 200-600 nm. Gallic acid and gallic acid-chitosan copolymer both show an obvious absorption peak in the wavelength range of 200-600 nm, but the maximum absorption peaks of the two do not overlap, the maximum absorption peak of the copolymer is offset, and the absorption peak of the copolymer is lower than the maximum absorption peak of gallic acid. It can be judged that under the induction of jet plasma, gallic acid is grafted on chitosan, and the benzene ring structure in the copolymer is not completely consistent with gallic acid, which eliminates the possibility of physical residue causing the absorption peak. Therefore, it is speculated that gallic acid has completed covalent grafting of chitosan under the induction of jet plasma.
[0076] (2) Infrared spectral characteristics 2 mg of chitosan, gallic acid, and gallic acid-chitosan copolymer were taken respectively, added with 200 mg of dry potassium bromide powder, mixed evenly and ground in an agate mortar, pressed into thin slices with a tablet press, and analyzed by Fourier transform infrared spectrometer at 4000 cm -1 ~400cm -1The results of the tests showed that the gallic acid-chitosan copolymers were successfully prepared in Examples 1 to 9.
[0077] Figure 3 : The Fourier transform infrared spectra of gallic acid-chitosan copolymer (Example 11), gallic acid, and chitosan. Figure 3 As shown, at 3350 cm -1 and 3244 cm -1 The OH and NH stretching vibrations observed at 1643 cm -1 and 1554 cm -1 The signal peaks at 1643 cm-1 correspond to the stretching vibration of the amide I band in chitosan and the NH bending vibration of the primary amine. However, the NH bending vibration of the primary amine in the copolymer is significantly weakened. -1 The N-acetyl stretching vibration at the position is significantly enhanced, which means that the carboxyl group in gallic acid reacts with the primary amine structure in chitosan in the form of an amide bond to form a new N-acetyl structure. At the same time, there is no structure such as O-acetyl in the infrared spectrum, indicating that gallic acid is not grafted on the hydroxyl group in chitosan. Therefore, it is proved that gallic acid is covalently grafted on the primary amine of chitosan in the form of an amide bond under the induction of jet plasma.
[0078] 2. Improved properties of gallic acid-chitosan copolymer (1) DPPH free radical scavenging rate Accurately weigh 2.0 mg DPPH and dissolve it in 50 mL anhydrous ethanol solution. Ultrasonicate for 3 minutes to fully dissolve it to prepare a 0.1 mM DPPH solution, and store it in the dark for later use. Dissolve the polysaccharide, ascorbic acid, and copolymer (obtained in Example 1) in 2% acetic acid solution to prepare solutions of different concentrations (0, 0.2, 0.4, 0.6, 0.8, 1 mg / mL). Take 2 mL of samples of a series of concentrations, add 2 mL of DPPH solution, store it in the dark at room temperature for 30 minutes, and measure the absorbance of each sample at 517 nm. The results are shown in Table 1. Figure 5 . Calculate according to the following formula: Among them, A0: 2.0 mL deionized water + 2.0 mL DPPH solution; A1: 2.0 mL sample solution + 2.0 mL DPPH solution; A2: 2.0 ml sample solution + 2.0 mL anhydrous ethanol.
[0079] like Figure 4As shown in the figure, chitosan solutions of all concentrations showed poor DPPH radical scavenging ability, with the highest being less than 5%. The DPPH radical scavenging rate of gallic acid-chitosan copolymer showed a concentration-dependent trend, and at a concentration of 1.0 mg / mL, the DPPH radical scavenging rate could reach 96.20 ± 2.01%, which was comparable to the effect of ascorbic acid at the same concentration. This proved that after plasma-induced gallic acid grafting chitosan, the in vitro DPPH scavenging rate of chitosan was significantly improved.
[0080] (2) ABTS free radical scavenging rate Mix equal amounts of 7 mM ABTS solution and 2.45 mM potassium persulfate and place in the dark for 12-16 h to prepare ABTS solution. Dilute the ABTS solution with anhydrous ethanol until its absorbance at 734 nm is 0.70 ± 0.02. Dissolve the polysaccharide, ascorbic acid, and copolymer (obtained in Example 1) in 2% acetic acid solution to prepare solutions of different concentrations (0, 0.2, 0.4, 0.6, 0.8, 1 mg / mL). Pipette 0.1 mL of sample of each concentration, add 3.9 mL of diluted ABTS bath solution, react at 30 °C in the dark for 20 minutes, and measure the sample absorbance at 734 nm. The results are shown in Table 1. Figure 5 . Calculate according to the following formula: Among them, A0: 0.1 mL deionized water + 3.9 mL ABTS solution; A1: 0.1 mL sample solution + 3.9 mL ABTS solution; A2: 0.1 ml sample solution + 3.9 mL anhydrous ethanol.
[0081] like Figure 5 As shown in the figure, chitosan solutions of all concentrations showed poor ABTS radical scavenging ability, only less than 10%; but after plasma-induced gallic acid grafting, the ABTS radical scavenging rate of gallic acid-chitosan copolymer showed a concentration-dependent trend, and at a concentration of 1.0 mg / mL, the ABTS radical scavenging rate could reach 46.45 ± 1.19%. This example demonstrates the significant effect of plasma-induced gallic acid grafting chitosan.
[0082] (3) Hydroxyl radical scavenging rate Dissolve the polysaccharide, ascorbic acid, and copolymer (obtained in Example 1) in 2% acetic acid solution to prepare solutions of different concentrations (0, 0.2, 0.4, 0.6, 0.8, 1 mg / mL). Take 1 mL of the sample of the series of concentrations, add 1 mL of FeSO4 (6 mM), 1 ml of salicylic acid-ethanol solution (6 mM), and 1 mL of H2O2 solution (6 mM) to it in sequence, mix well, react at 37 °C for 30 min, and measure the absorbance at 510 nm. Calculate according to the following formula: Among them, A0: 1.0 mL deionized water + 1.0 mL FeSO4 solution + 1.0 mL salicylic acid-ethanol solution + 1.0 mL H2O2 solution; A1: 1.0 mL sample solution + 1.0 mL FeSO4 solution + 1.0 mL salicylic acid-ethanol solution + 1.0 mL H2O2 solution; A2: 1.0 mL sample solution + 1.0 mL FeSO4 solution + 1.0 mL salicylic acid-ethanol solution + 1.0 mL deionized water.
[0083] Depend on Figure 6 It can be seen that all concentrations of chitosan solutions showed poor hydroxyl radical scavenging ability, with the highest being less than 3%. However, the hydroxyl radical scavenging rate of the gallic acid-chitosan copolymer in Example 1 showed the same concentration-dependent trend as the ascorbic acid standard antioxidant. And when the copolymer concentration reached 1.0 mg / mL, the hydroxyl radical scavenging rate could reach 19.28 ± 1.71%. This shows that plasma-induced gallic acid grafted chitosan has better in vitro hydroxyl radical scavenging ability than natural chitosan, indicating that it is feasible to improve the physicochemical properties of chitosan by inducing gallic acid grafted chitosan through room temperature plasma.
[0084] (4) Solubility 0.05 g of gallic acid-chitosan copolymer and chitosan prepared in Example 9 were accurately weighed and mixed with 5 mL of deionized water, respectively. After magnetic stirring at 25 °C for 5 hours, the mixture was centrifuged and the supernatant was collected to obtain a soluble component. After the soluble component was freeze-dried, the weight of the soluble component was accurately weighed and the solubility was calculated. Figure 7 .
[0085] Depend on Figure 7 It can be seen that chitosan is soluble in water at 2.01 ± 0.13%, and the gallic acid-chitosan copolymer in Example 1 is soluble in water at 54.83 ± 0.65%. It can be seen that the solubility of chitosan is significantly improved after being modified by plasma and grafted with gallic acid.
[0086] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A plasma-induced polyphenol-polysaccharide copolymerization method, characterized in that: The following steps are involved: Step S1: dissolving polysaccharides and polyphenols in a solvent, and mixing them to obtain a mixed solution; Step S2: Plasma treatment is introduced into the mixed solution for a period of time; Step S3: taking the mixed liquid after the plasma treatment and stirring it; Step S4: Dialysis and freeze-drying to obtain a polyphenol-polysaccharide copolymer.
2. The method for copolymerizing polyphenols and polysaccharides based on plasma induction according to claim 1, characterized in that: In step S2, treatment is performed by nitrogen plasma.
3. A method for copolymerizing polyphenols and polysaccharides based on plasma induction as claimed in claim 1 or 2, characterized in that: In step S2, plasma treatment is performed by using a jet plasma spray gun, specifically, the exhaust port of the jet plasma spray gun is placed below the liquid surface of the mixed liquid to perform plasma discharge.
4. The method for copolymerizing polyphenols and polysaccharides based on plasma induction according to claim 1, characterized in that: The plasma treatment time is 5 to 30 min.
5. A method for preparing a plasma-induced gallic acid-chitosan copolymer, characterized in that: The following steps are involved: (1) dissolving chitosan and gallic acid in a solvent and mixing them to obtain a mixed solution; the molar ratio of chitosan to gallic acid is 1:1-6; (2) placing the exhaust port of the jet plasma spray gun below the liquid surface of the mixed solution and turning on the spray gun to perform plasma discharge; wherein nitrogen gas is introduced into the jet plasma spray gun; (3) quickly placing the mixed solution after plasma treatment in a high-temperature water bath for stirring and reaction; (4) Dialysis and freeze-drying to obtain gallic acid-chitosan copolymer.
6. The preparation method according to claim 5, characterized in that: In step (1), the solvent is an acetic acid solution, and the mass percentage of the acetic acid solution is 0.5-2%.
7. The preparation method according to claim 5, characterized in that: In step (2), the exhaust port of the jet plasma spray gun is placed 1 to 4 cm below the liquid surface of the mixed solution.
8. The preparation method according to claim 5 or 7, characterized in that: In step (2), the nitrogen gas is introduced at a flow rate of 2 to 8 L / min.
9. The preparation method according to claim 5 or 7, characterized in that: In step (2), the discharge power of the jet plasma spray gun is 100-130 W, and the discharge time is 5-30 min.
10. The preparation method according to claim 5, characterized in that: In step (3), the temperature of the high temperature water bath is 60-90° C., and the stirring time is 1-4 h.
Citation Information
Patent Citations
Novel water soluble chitosan derivative and preparation and application thereof
CN101974102A
Preparation method of chitosan-gallic acid copolymer and application
CN106084088A
Chitosan-gallic acid graft copolymer as well as preparation method and application thereof
CN112961264A
Preparation and purification method of hydroxybutyl chitosan-gallic acid
CN116143954A
Preparation method of propolis polyphenol grafted chitosan compound
CN117447623A